2014
DOI: 10.1007/s00109-014-1219-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of SMP30 modulates NF-κB through protein tyrosine kinase/phosphatase balance

Abstract: SMP30-deficient mice induced a shorter lifespan and redox changes. Overexpression of SMP30 prevented oxidative stress insults. The depletion of SMP30 increased redox-related PTK/PTP imbalance and PP1/PP2A inactivation. The depletion of SMP30 caused an elevation of NF-κB-responsive inflammatory markers. SMP30 may be a potent inhibitory protein against oxidative stress and chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…It is hypothesized that the activation of SIRT1 promotes the deacetylation of Nrf2, improving the stability of this transcription factor [ 21 , 22 ]. The senescence marker protein-30 (SMP30), expressed mainly in the liver and kidney, is considered a biomarker of aging process, since its levels decrease with age [ 23 , 24 ]. It is suggested that SMP30 is able to suppress oxidative stress and consequently decrease NFkB levels, therefore, the decrease of SMP30 protein with age leads to an increase of oxidative damage and inflammatory response, which promotes aging [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that the activation of SIRT1 promotes the deacetylation of Nrf2, improving the stability of this transcription factor [ 21 , 22 ]. The senescence marker protein-30 (SMP30), expressed mainly in the liver and kidney, is considered a biomarker of aging process, since its levels decrease with age [ 23 , 24 ]. It is suggested that SMP30 is able to suppress oxidative stress and consequently decrease NFkB levels, therefore, the decrease of SMP30 protein with age leads to an increase of oxidative damage and inflammatory response, which promotes aging [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the body weight, plasma IL-6 levels, and plasma LDL levels were higher in the db/db mice than in the lean mice, and these were improved after stem cell replacement, suggesting that these parameters were related to the expression of SMP30 in the liver. SMP30 has been shown to modulate the balance of protein tyrosine kinase and protein tyrosine phosphates, and also to regulate NF-κB related inflammatory activity [ 17 ]. One report showed that, 30 min after glucose administration, blood glucose levels rose higher and insulin levels fell lower in SMP30-deficient mice than in wild-type mice [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between SMP30 expression and oxidative stress is critical for understanding the mechanisms of senescence. Moreover, the activities of inflammatory NF-kB are higher in SMP30-deficient mice, suggesting that SMP30 prevents oxidative stress and chronic inflammation [ 17 ]. Indeed, one report indicates that high levels of oxidative stress caused abnormal plasma lipid metabolism and hepatic lipid accumulation in the SMP30 and superoxide dismutase 1-deficient mouse [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mouse lung tissues were obtained from the Aging Tissue Bank (Pusan, Korea). Senescence marker protein (SMP)30 Y/+ and SMP30 Y/- mice were described previously [ 16 ]. Total RNA was purified using the RNeasy Mini Kit (Qiagen), according to the manufacturer's recommended protocol.…”
Section: Methodsmentioning
confidence: 99%